Baolier Capsule’s Secret Weapon: Piperine Boosts Cholesterol Excretion to Combat Atherosclerosis - Wei M; LYu P; Li P; Hu J; Wu R; Ouyang Q; Guo K (Drug Design, Development and Therapy)
Mengqiu Wei,1,* Ping LYu,2,* Peng Li,3 Jing Hu,4 Ruozhuo Wu,5 Qingqing Ouyang,6 Kai Guo7 1Intensive Care Unit, Zhongshan City People’s Hospital, Zhongshan, 528400, People’s Republic of China; 2Department of Cardiovascular Surgery, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 3Department of Geriatrics, The Fifth Affiliated Hospital of Sun Yat-Sen University, Zhuhai, 519000, People’s Republic of China; 4Department of Cardiology, Jiangxi Provincial People’s Hospital, The First Affiliated Hospital of Nanchang Medical College, Nanchang, 330006, People’s Republic of China; 5School of Biological and Pharmaceutical Engineering, Wuhan Huaxia Institute of Technology, Wuhan, 430223, People’s Republic of China; 6Department of Rheumatology and Immunology, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 7Department of Cardiology, The Seventh Affiliated Hospital of Southern Medical University, Southern Medical University, Foshan, 528244, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kai Guo; Qingqing Ouyang, Email guokai154556@i.smu.edu.cn; ouyangqing1988@163.comPurpose: The Baolier capsule (BLEC) is a proprietary Mongolian medicine administered for treating hypercholesterolemia and atherosclerosis (AS). However, the therapeutic effects, primary bioactive ingredients, and potential mechanisms underlying hypercholesterolemia and AS remain unclear. This study aimed to investigate the pharmacological effects, principal active ingredients, and mechanisms of BLEC against hypercholesterolemia and AS.Methods: Adeno-associated virus tail vein injection was utilized to construct liver-specific LXRα knockout ApoE−/− mice. A high-fat diet was utilized to feed ApoE−/− mice to build hyperlipidemia and AS mouse models. The aorta or liver stained with Oil Red O was used to assess the effect of the drugs on AS or fatty liver formation after the oral administration of BLEC, piperine, statins, or ezetimibe to the mice following the experimental protocol. Biochemical assays were utilized to evaluate the effect of the drugs on serum lipid levels and cholesterol efflux indicators. Transcriptomics was employed to investigate the effect of BLEC on liver gene expression levels. HPLC-MS/MS was used to determine BLEC and its major components in the liver. Western blotting or quantitative reverse transcription polymerase chain reaction was conducted to detect LXRα, ABCA1, ABCG5, ABCG8, and CYP7A1 expression.Results: Here, we revealed that BLEC decreases lipid levels in the serum and liver, as well as decelerates AS by promoting cholesterol excretion. BLEC and piperine, which are the main components exposed in the target liver tissue, activate LXRα to upregulate ABCA1, ABCG5, ABCG8, and CYP7A1, which promotes cholesterol transport to high-density lipoprotein and excretion to bile and feces. Notably, piperines demonstrated synergistic beneficial effects with atorvastatin or ezetimibe, which are two widely used hypocholesterolemic and anti-atherosclerotic drugs.Conclusion: BLEC and its main active ingredient, piperine, promote cholesterol excretion, reduce serum cholesterol levels, inhibit AS, and exhibit good clinical application value and prospects. Keywords: Baolier Capsule, atherosclerosis, hypercholesterolemia, cholesterol excretion, piperine, LC-MS/MS, transcriptomics